A study of classroom concordancing in the Greek context: Data-driven grammar teaching and adolescent EFL learners - Rapti, Nikoletta (2010)
This thesis examines the impact of Data-driven learning (DDL) or classroom concordancing on a group of adolescent students in Greece seeking to investigate the degree of motivation to learn grammar when involved in DDL and the effectiveness of DDL in the teaching and learning of grammar. The study introduced concordance-based grammar materials to the experimental group, whereas a conventional grammar book was used with the control group, examining common grammar items and patterns. The analysis of classroom data gathered during DDL sessions offered insights into the improved noticing skills of the participants but also into the difficulties when involved in DDL with regard to unknown vocabulary and the Key Word in Context (KWIC) concordance format, which underlined the need for considerable teacher guidance. The qualitative evidence drawn from questionnaires and interviews suggested that the majority of the participants acknowledged the contribution and potential of corpora, but the degree of motivation to study grammar further varied. Most learners also expressed their preference for concordance-based learning, rather than their previous mostly passive learning experience, and further access to corpora, but without total abandonment of the conventional grammar book. The qualitative evidence was supplemented with analysis of test performances of the two groups, according to which more participants of the experimental group scored higher than those of the control group in each test. All these findings pointed to important gains and represent a preliminary step in the development of corpus-based grammar teaching to EFL adolescent learners.